(untitled) (Journal of Nepal Geological Society, 2011)
Petrological study was carried out for the first time on the metabasites of the Lesser Himalaya in central Nepal. The metabasites are mostly tholeiitic basalts emplaced in the elastic sediments as supracrustal dikes and sills, and later metamorphosed together with the host rocks. They contain almost a constant mineral assemblage of Ca-amphiboles + plagioclase + biotite + quartz ± epidote± chlorite + (Fe-Ti oxides). Amphiboles in the form of porphyroblasts show chemical zonation with actinolite/magnesiohomblende cores, tschermakite/ferro-tschermakite rims, and magnesio-hornblende margins. The cores of porphyroblasts are pre-kinematic and were probably formed prior to the Tertiary Himalayan orogeny. The porphyroblast rims and the matrix amphiboles are syn-kinematic and were formed during the Upper Main Central Thrust activity in the Tertiary period. The compositions of both the porphyroblast rims and matrix amphiboles change from actinolite in the chlorite zone to magnesium hornblende in the biotite zone and totschermakite/ferro-tschermakite in the garnet zone. The systematic changes in amphibole compositions as well as petrographic characteristics of metabasites confirm the classical concept of increasing metamorphic grade structurally upwards to the Upper Main Central Thrust in the Lesser Himalaya. Application of hornblende-plagioclase thermobarometry shows a coherent prograde P-T path in zoned amphiboles. The cores of amphibole porphyroblasts were formed at average peak temperature of 540"C and at pressure of 3 kbar. The porphyroblast rims and matrix amphiboles were recrystallized at average peak temperatures of 570°C in the biotite zone and 630°C in the garnet zone at pressure of 6 kbar. The metabasites petrology is in favor of the tectono-metamorphic models that relate the inverted metamorphism with thrusting along the Upper Main Central Thrust and coeval inversion of isoiliem1S. It is suggested that published amphibole cooling ages from the Nepalese Lesser Himalaya based on simples, homogeneous mineralogy should be reinterpreted in view of the presence of polygenetic amphiboles with heterogeneous composition.